Pengaruh Kredibilitas Influencer Terhadap Minat Beli Ulang yang Dimediasi oleh Cita Merek Skincare The Originote - Vina Aprilia Purwadi; Siti Herawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to examine the influence of influencer credibility on repurchase interest mediated by the brand image of the originote skincare product, especially in the audience of detective doctors. The background of this study is based on the indication of a decrease in interest in rebuying. With a quantitative approach, the study included 98 people who were selected based on predetermined standards. Questionnaires that have gone through validity and reliability testing function as research instruments. All such instrument items are valid and reliable and according to the test results, data collection can be resumed. Furthermore, classical assumption testing is used to assess the data derived from questionnaire answers. The findings of this test show that the data have a normal distribution, do not show multicollinearity, and are free of heteroscedasticity. The data were then analyzed using simple regression analysis, multiple regression, and the Sobel test via SPSS software. The findings of the study show that Influencer Credibility has a positive and significant effect on Brand Image. The credibility of the influencer has no effect on the Repurchase Interest. Brand Image has a positive and significant effect on Repurchase Interest. Brand Image mediates the influence of Influencer Credibility on Repurchase Interest.